Analisis Kinerja Anggaran Pendapatan dan Belanja Daerah Pada Badan Pendapatan Daerah Kabupaten Bengkalis Tahun Anggaran 2017-2018 - Ema Nirwana (Politeknik Negeri Bengkalis, 2020)
The purpose of this research is aimed to analysis financial working performance of Regional Revenue Agencies in Bengkalis Government in Fiscal Year 2017-2018. The data that used in is this research was secondary data from primer source that would get from Annual Report of Regional Revenue Agencies in Bengkalis Government in form of has been collected, procced and also has been audited by Republik Indonesia Financial Audit Agency in FiscalÂ 2017-2018. The analysis tools were Analysis of APBD Performance through the measurement ratios of financial performance. Specially this risearch used Performance Growth of PAD Analysis, Effectiveness of PAD Analysis, Efficiency of PAD Analysis and then Performance Growth Government Spending and Efficiency of Government Spending Analysis based on LRA, Fiscal 2017-2018. The result of this research conclude that : (1) Based on Performance Growth of PAD Analysis, that showed negative growth. It caused by several economic problem include external and internal Regional Revenue Agencies in Bengkalis Government (2) Seen from Effectiveness of PAD Analysis, the Effectivity of PAD organizing is quite effective for Fiscal 2017 but if we compareÂ for Fiscal 2018 that showed not effective. (3) Seen from Efficiency of PAD Analysis, the Efficiency of PAD organizing was very efficient for Fiscal 2017-2018. (4) Based on Performance Growth of Government Spending Analysis, that showed the amount of Government Spending has decreased for Fiscal 2017-2018. (5) Seen from Efficiency of Government Spending Analysis, the Efficiency of Government Spending organizing was very efficient for Fiscal 2017-2018.Â Keyword : Performance APBD Analysis, PAD, Government Spending